Introduction to structural aluminium design - Müller, Ulrich (Whittles, 2010)
Annotation This book deals with the use of aluminium for structural and non-structural applications and provides an introduction to designing structures made from aluminium or aluminium alloy elements. It comprises a ready reference to the material properties and behaviour of aluminium, and its use in structural design. In the context of information about the material itself,fabrication, structural design and corrosion, structural analysis, serviceability, element design and fatigue the author considers the strengths of designing with aluminium alloy members and how any weaknesses can be overcome. Reference is made throughout to EN 1999, Eurocode 9, and its design methods are discussed and illustrated.With most of its structural strength properties close to steel and with consideration for the special properties of aluminiumalloys, there is considerable scope to make better use of this material in construction. Many years of working with aluminiumhave provided the author with the knowledge to avoid pitfalls and problems in design, fabrication and protection of structures,thus avoiding costly remedial work.
Keywords: Aluminum construction.; Aluminum, Structural.; Structural design.; elektronické knihy; electronic books